2020
DOI: 10.1080/0284186x.2020.1769858
|View full text |Cite
|
Sign up to set email alerts
|

Survival after breast cancer in women with type 2 diabetes using antidiabetic medication and statins: a retrospective cohort study

Abstract: Background: We assessed survival of breast cancer in women with type 2 diabetes (T2D) treated with metformin, other types of antidiabetic medication (ADM) and statins. Materials and Methods: The study cohort consisted of women with T2D and diagnosed with breast cancer in Finland in 1998─2011. Mortality rates from breast cancer and other causes were analysed by Cox models, and adjusted hazard ratios (HRs) with 95% confidence intervals (Cls) were estimated in relation to the use of different types of medication.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
(85 reference statements)
1
13
0
Order By: Relevance
“…Extrapolation of the findings of this trial to patients with diabetes requires caution because of differing metabolic status (eg, glucose control, insulin resistance, obesity) of patients with vs without diabetes, and reports that breast cancer outcomes are poorer in patients with diabetes for reasons that are not fully understood but may be related to the biological effect of diabetes on breast cancer, delayed breast cancer diagnosis, effects of comorbidity, poor treatment adherence, or other factors. Observational studies involving patients with breast cancer and diabetes have reported inconsistent associations of metformin treatment for diabetes with breast cancer outcomes . A meta-analysis reported better overall and cancer-specific survival in patients with breast cancer and diabetes who received metformin vs other diabetes treatments; however, all of the included observational studies were susceptible to methodological limitations that may have affected results, notably treatment allocation and survival biases .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extrapolation of the findings of this trial to patients with diabetes requires caution because of differing metabolic status (eg, glucose control, insulin resistance, obesity) of patients with vs without diabetes, and reports that breast cancer outcomes are poorer in patients with diabetes for reasons that are not fully understood but may be related to the biological effect of diabetes on breast cancer, delayed breast cancer diagnosis, effects of comorbidity, poor treatment adherence, or other factors. Observational studies involving patients with breast cancer and diabetes have reported inconsistent associations of metformin treatment for diabetes with breast cancer outcomes . A meta-analysis reported better overall and cancer-specific survival in patients with breast cancer and diabetes who received metformin vs other diabetes treatments; however, all of the included observational studies were susceptible to methodological limitations that may have affected results, notably treatment allocation and survival biases .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reported better overall and cancer-specific survival in patients with breast cancer and diabetes who received metformin vs other diabetes treatments; however, all of the included observational studies were susceptible to methodological limitations that may have affected results, notably treatment allocation and survival biases . It has been suggested that metformin may act by alleviating the adverse breast cancer prognosis associated with diabetes, possibly through better diabetes control or due to selection of patients with less severe diabetes to receive metformin, rather than through a direct antitumor effect. Because metformin is effective in type 2 diabetes, the results presented herein should not affect the use of metformin to treat diabetes in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 A retrospective cohort study also showed that breast cancer patients with preDM given insulin analogs had higher mortality rates than those taking other oral hypoglycemic drugs. 28 Furthermore, it is plausible that synthetic insulin by subcutaneous injection may lead to altered pharmacokinetic profiles and different affinities for receptor-binding, such as insulin receptors, IGFR1 and hybrid receptors, bringing about a stronger cancer-promoting effect than endogenous insulin. 29–31 In addition, in our study, those who had received insulin treatment usually had higher fasting glucose levels, suggesting that they had poor glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…8 While this precedence was promising, it is notable that there were some observational studies that did not support metformin's therapeutic potential. 9 Furthermore, in the metastatic breast cancer setting, randomized trials showed no oncologic survival benefit with the addition of metformin to standard regimens. 10,11 The MA.32 randomized clinical trial, an international study of Goodwin et al, recruited non-diabetic patients diagnosed with high-risk breast cancer between 2010 and 2013.…”
mentioning
confidence: 99%